Evaluating the impact of an organic nitrification inhibitor on nitrogen availability and its influence on microbial population in paddy soil - Rajkishore, Subramani Krishnaraj; Sivakumar, Uthandi; Ashok , Raina; Maheshwari, Muthunalliyappan; Sivasankari Devi, Thambusamy; Sriram, Lakshmanan (Plant Science Today, 2025)
An incubation study was conducted to estimate the potential inhibition rates of nitrification using phytonim-coated fertilizers like urea and ammonium sulfate (AS) at different concentrations viz., 100 % and 65 % of the recommended dosage (RD) and additionally ammonifying bacteria (AB) was added with urea as one of the treatments. Samples were taken at 13 different intervals in a 45-day incubation experiment. Applying phytonim-coated fertilizers delayed the nitrification process for 35 days, improving the soils' available N. Ammonia oxidation and nitrite oxidation rates were reduced by 14 % and 35 % in phytonim-coated urea, 11 % and 23 % in phytonim-coated urea + AB and 24 % and 45 % in phytonim-coated AS, respectively over uncoated fertilizers. Nitrate reductase activity was reduced by 17 %, 16 % and 21 % in phytonim-coated fertilizers like urea, AS and urea + AB compared to uncoated fertilizers. Soil urease activity was inhibited in phytonim-coated urea (100 % RD and 65 % RD) of 9.6 % and 7.4 %, respectively, whereas 5.7 % and 6.7 % increased urease activity were observed in phytonim-coated urea + AB (100 % RD) and coated urea + AB (65 % RD). Increased soil dehydrogenase activity and FDA hydrolysis of 20 % and 15 % were observed in phytonim-coated urea, 15 % and 18 % in phytonim-coated urea + AB (100 % RD) and 17 % and 16 % in phytonim-coated AS over uncoated fertilizers. Results show that phytonim-coated AS (100 % RD) (T8) has inhibited nitrification most, followed by phytonim-coated urea (100 % RD) (T4) during the incubation period. This study concludes that applying organic nitrification inhibitors inhibited the nitrification and denitrification rates, affected the urea hydrolysis and positively affected the microbial population.